The effects of different dry roast parameters on peanut quality using an industrial belt-type roaster simulator. (1st February 2018) - Shi, Xiaolei; Dean, Lisa O.; Davis, Jack P.; Sandeep, K.P.; Sanders, Timothy H.
Highlights: A pilot plant roaster simulated peanut roasting in commercial belt roasters. Highest roast peanut flavor intensity was found in the medium roast. Moisture content was lower at the lowest roast temperature. No temperature impact on tocopherols with dark and medium roasting. Yield stress of peanut paste increased with dark roast color. Abstract: Peanuts roasted to equivalent surface colors at different temperature/time combinations can vary substantially in chemical and physical properties related to product quality. This study used a pilot plant scale roaster that simulates the configurations of one of the most common industrial roaster, a multi-zone belt roaster. Jumbo-size runner-type peanuts were systematically roasted at 5 temperatures (149–204 °C) to three Hunterl -values of 53, 48.5, and 43, corresponding to light, medium, and dark roasts. Moisture and tocopherol contents were more closely correlated with roast color rather than temperature, with exceptions at 149 °C. Moisture decreased with darker roast color, while the total tocopherols were greatest in peanut oils with darker colors. Yield stress of peanut pastes increased as the color darkened, indicating spreadability correspondingly decreased with darker roast colors. The overall flavor of roasted peanuts was found to be optimized at 177 °C/15 min with the medium roast color.